1999
DOI: 10.1063/1.123358
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN metal–semiconductor–metal photodiodes

Abstract: We report on the fabrication and characterization of AlGaN metal–semiconductor–metal photodiodes with sharp cutoff wavelengths from 365 to 310 nm. The detectors are visible blind, with an ultraviolet/visible contrast of about 4 orders of magnitude. The photocurrent scales linearly with optical power for photon energies both over and below the band gap, supporting the absence of photoconductive gain related to space-charge regions. No persistent photoconductivity effects have been detected. Time response is lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
4

Year Published

1999
1999
2002
2002

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 12 publications
2
64
1
4
Order By: Relevance
“…2 shows the spectral response of GaN MSM photodiodes at 1 V and 5 V bias. The responsivity is quite flat over the bandgap, with a sharp cutoff wavelength that shifts to shorter wavelengths with increasing Al content [7]. A visible rejection of four to five orders of magnitude is obtained at 5 V, and the same behavior is observed for higher bias.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…2 shows the spectral response of GaN MSM photodiodes at 1 V and 5 V bias. The responsivity is quite flat over the bandgap, with a sharp cutoff wavelength that shifts to shorter wavelengths with increasing Al content [7]. A visible rejection of four to five orders of magnitude is obtained at 5 V, and the same behavior is observed for higher bias.…”
Section: Resultssupporting
confidence: 57%
“…The recent demonstration of Al x Ga 1± ±x N photoconductors [1,2], p±i±n photodiodes [3], Schottky barrier photodetectors [4,5], and metal±semiconductor±metal (MSM) photodiodes [6,7] has confirmed that Al x Ga 1± ±x N alloy is the most promising semiconductor for visible-blind ultraviolet (UV) detection, in the range from 365 to 200 nm. MSM photodiodes present some advantages over other photovoltaic detectors, like their fabrication simplicity, low dark current, high bandwidth capability, and suitability for integration with field effect transistors.…”
Section: Introductionmentioning
confidence: 87%
“…The cutoff wavelength of Al x Ga 1Àx N detectors can be tuned from 365 to 200 nm by changing the Al mole fraction of the alloy. AlGaN photoconductors [1,2], p±i±n photodiodes [3], Schottky barrier detectors [4,5] and metal±semiconductor±metal photodiodes [6] have recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Good quality metal-semiconductormetal photodiodes were successfully fabricated on these samples. 6 Micro-Raman measurements have been performed in backscattering configuration at room temperature. An incident beam at 514.5 nm, well below the fundamental band gap of the material, was focused onto a region of ϳ1 m diameter, and the scattered light was analyzed through a Dilor triple spectrometer provided with a charge coupled device detector.…”
Section: Methodsmentioning
confidence: 99%